System Testing and Performance Evaluation of an MQTT-Based IoT Monitoring System for Crop Cultivation (Faculty of Engineering, Universitas Tanjungpura, 2026)
Agriculture is a crucial component of Indonesia's economy and food security. However, farmers have been using conventional techniques, such as planting according to a fixed timetable that is unaffected by weather or temperature. This will negative effect on the quality and yields of crops. Thus, a device is needed that can provide information about the weather or temperature. The message queuing telemetry transport (MQTT) is very helpful because it send data from the microcontroller to the display. This research aims to develop a prototype that displays measurement data utilizing MQTT and Node-RED, along with performance evaluations including latency, packet loss, and energy efficiency. This study employs an experimental approach that starts with a schematic design, followed by the installation and evaluation of a monitoring system. The outcome of this research indicates that the prototype worked performed well in an open farming field. System performance was assessed in terms of latency, packet loss, and energy efficiency. The results demonstrate stable operation during a 10-day field deployment, with an average latency of approximately 1.3 s, a packet loss rate of 1.38% and average power consumption of 1.25 W over 24 hours of continuous operation. These findings indicate that the proposed system is suitable for real-time agricultural monitoring under open-field conditions. The study emphasizes deployment feasibility and system-level performance rather than detailed agronomic analysis providing insights into the use of MQTT-based IoT solutions for open-field precision agriculture